The Effects of Peripheral Inflammation on the Brain—A Neuroimaging Perspective. Issue 1 (January 2022) - Millett, Caitlin E.; Burdick, Katherine E.; Kubicki, Marek R.
Abstract : Abstract: In the field of neuropsychiatry, neuroinflammation is one of the prevailing hypotheses to explain the pathophysiology of mood and psychotic disorders. Neuroinflammation encompasses an ill-defined set of pathophysiological processes in the central nervous system that cause neuronal or glial atrophy or death and disruptions in neurotransmitter signaling, resulting in cognitive and behavioral changes. Positron emission tomography for the brain-based translocator protein has been shown to be a useful tool to measure glial activation in neuropsychiatric disorders. Recent neuroimaging studies also indicate a potential disruption in the choroid plexus and blood-brain barrier, which modulate the transfer of ions, molecules, toxins, and cells from the periphery into the brain. Simultaneously, peripheral inflammatory markers have consistently been shown to be altered in mood and psychotic disorders. The crosstalk (i.e., the communication between peripheral and central inflammatory pathways) is not well understood in these disorders, however, and neuroimaging studies hold promise to shed light on this complex process. In the current Perspectives article, we discuss the neuroimaging insights into neuroimmune crosstalk offered in selected works. Overall, evidence exists for peripheral immune cell infiltration into the central nervous system in some patients, but the reason for this is unknown. Future neuroimaging studies should aim to extend our knowledge of this system and the role it likely plays in symptom onset and recurrence.